2020
DOI: 10.1186/s12978-020-00955-2
|View full text |Cite
|
Sign up to set email alerts
|

Count data regression modeling: an application to spontaneous abortion

Abstract: Background In India, around 20,000 women die every year due to abortion-related complications. In count data modeling, there is sometimes a prevalence of zero counts. This article is concerned with the estimation of various count regression models to predict the average number of spontaneous abortions among women in Punjab and few northern states in India. The study also assesses the factors associated with the number of spontaneous abortions. Methods This study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…It indicates that Poisson regression is not an appropriate model for our data as alpha is significant which shows negative binomial regression is preferred over poisson regression and insignificant Vuong test shows negative binomial regression model is preferred over zero-inflated negative binomial regression model (Hardin & Hilbe, 2014;Shaaban et al, 2021;Xu, Zhu, & Han, 2017). We checked the goodness of fit between count models with the help of Akaike information criterion (AIC) and Bayesian information criterion (BIC) (Ismail & Zamani, 2013;Shaaban et al, 2021;Verma, Swain, Singh, & Khetan, 2020;Xu et al, 2017). AIC and BIC value of negative Negative binomial regression result shows the effect of household cooking energy poverty on number of children with acute respiratory infection count distribution.…”
Section: Empirical Results On the Effect Of Household Cooking Energy ...mentioning
confidence: 99%
“…It indicates that Poisson regression is not an appropriate model for our data as alpha is significant which shows negative binomial regression is preferred over poisson regression and insignificant Vuong test shows negative binomial regression model is preferred over zero-inflated negative binomial regression model (Hardin & Hilbe, 2014;Shaaban et al, 2021;Xu, Zhu, & Han, 2017). We checked the goodness of fit between count models with the help of Akaike information criterion (AIC) and Bayesian information criterion (BIC) (Ismail & Zamani, 2013;Shaaban et al, 2021;Verma, Swain, Singh, & Khetan, 2020;Xu et al, 2017). AIC and BIC value of negative Negative binomial regression result shows the effect of household cooking energy poverty on number of children with acute respiratory infection count distribution.…”
Section: Empirical Results On the Effect Of Household Cooking Energy ...mentioning
confidence: 99%
“…Previous evidence reported that women with the lowest wealth status had lower odds of pregnancy loss than women with the highest wealth status for a unit change in gravidity. An important relationship with gravidity discovered indicates that the association between wealth status and pregnancy loss depends on the woman's level of gravidity (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological studies and statistical methods of analysis, count regression analysis techniques are better for count response interests such as number of infants’ deaths [ 37 ]. Count regression models are suitable for the count-dependent variable, and the models are used to assess the prevalence or frequency of outcome interest over time [ 38 ]. These models can cope with the dependent variable’s non-normality, and the model does not require the dependent variable to be transformed or dichotomized.…”
Section: Study Variablesmentioning
confidence: 99%